Evaluation of Fitness Level of Elementary School in Surabaya through MFT Test - Reza Apriansah, Reza (Proceeding of International Joint Conference on UNESA, 2025)
This study aimed to evaluate the physical fitness level of elementary school students in Surabaya using the Multistage Fitness Test (MFT). A descriptive quantitative method was applied to 120 students in grades 4-6 with data collection through a 20-meter shuttle run protocol synchronized with bleep audio. VO2Max results were analyzed using SPSS 25.0 to categorize fitness status based on Ministry of Education and Culture standards. The data showed 45% of the sample fell into the “deficient” (VO2Max 25-35 mL/kg/min) and 30% “very deficient” (<25 mL/kg/min) categories, with only 15% reaching the “good” category. Comparative analysis revealed significant differences between male (mean VO2Max 32.7±4.2) and female (28.9±3.8) students. , VO2max in children is a reliable indicator of general health, with lower VO₂max values linked to a higher chance of developing metabolic and cardiovascular disorders in later life. According to research, during childhood and adolescence, VO₂max tends to climb with age, with boys often showing a more noticeable rise than girls. However, research is still being done to determine whether exercise training can help kids increase their VO₂max. Although children can be aerobically trained, the amount of improvement in VO₂max that occurs after physical training is often less than that of adults and depends on a number of factors, including age, maturation, and the particulars of the training regiment. Children's VO₂max is also influenced by a number of clinical, functional, sociodemographic, and behavioral factors, such as motivation, physical activity levels, and cardiac and pulmonary function. The importance of VO₂max as a crucial indicator for pediatric health assessment and intervention is highlighted by the fact that children with chronic illnesses, such as hereditary heart disorders, frequently have much lower VO₂max values than their healthy peers